Ultrasonographic monitoring of response to therapy in polymyalgia rheumatica. Issue 5 (22nd September 2009) - Jiménez-Palop, M; Naredo, E; Humbrado, L; Medina, J; Uson, J; Francisco, F; García-Yebenes, M J; Garrido, J
Abstract : Objective: To assess the responsiveness of ultrasound (US) inflammatory findings in the shoulder and hip of patients with polymyalgia rheumatica (PMR) who started treatment with corticosteroids. Methods: Fifty-three patients with active PMR who started treatment with prednisone in six Spanish centres were prospectively studied. The patients underwent clinical, laboratory and US assessment at baseline, 4 and 12 weeks. The US investigation consisted of detection and quantification of inflammatory findings in the shoulder and hip. The responsiveness of clinical, laboratory and US parameters was tested by the standardised response mean. Intraobserver and interobserver reliability between US investigators was assessed. Results: At baseline, 34 patients (69%) had inflammation in at least one bilateral site. During the follow-up period, clinical, laboratory and US variables showed a parallel decrease. A significant decrease in US inflammatory parameters was found at week 4 (p<0.001). After 4 and 12 weeks of treatment with corticosteroids, US inflammatory findings showed similar or better sensitivity to change than clinical and laboratory markers of PMR activity. Intraobserver and interobserver intraclass correlation coefficients were 0.96 and 0.99, respectively (p<0.05). Conclusion: US may be a responsive additional tool in monitoring the response to corticosteroids in patients with PMR in daily practice and multicentre trials.